2020
DOI: 10.3389/fvets.2020.00548
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Meloxicam Between Healthy Post-partum vs. Mid-lactation Dairy Cattle

Abstract: Lactating dairy cattle are at risk for various painful conditions throughout their life, such as lameness, parturition, mastitis, and metabolic disorders. These conditions necessitate adequate methods of analgesia to address welfare concerns through efficacious pain mitigation. As no method of analgesia has been approved for lactating dairy cattle, to date, research is necessary to determine effective pain management strategies for dairy cattle. In both the European Union and Canada, meloxicam has been approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…This also suggests that excretion is not impacted by the increased dose. Oral clearance was also similar to cattle studies using a 1 mg/kg PO dosing regimen [19,22]. Plasma concentrations following 30 mg/kg meloxicam administrations at 120th hour were similar to the Cmax reported in 1 mg/kg dose studies in cattle.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This also suggests that excretion is not impacted by the increased dose. Oral clearance was also similar to cattle studies using a 1 mg/kg PO dosing regimen [19,22]. Plasma concentrations following 30 mg/kg meloxicam administrations at 120th hour were similar to the Cmax reported in 1 mg/kg dose studies in cattle.…”
Section: Discussionsupporting
confidence: 75%
“…The C max in the present study was similar to sows dosed with the same dose (30 mg/kg meloxicam PO) approaching 100 ug/mL [18]. Plasma C max was approximately 30 times higher than the reported C max for studies using 1 mg/kg dose in cattle that reported plasma C max ranging from 1.45-3.10 µg/mL [19][20][21][22][23]. The much higher C max and longer T max were likely directly due to the delivered dose being 30 times higher.…”
Section: Discussionsupporting
confidence: 65%
“…The AUC 0-inf generally appears to be greater for cattle [14,15,[19][20][21][32][33][34][35][36] than for the sheep in our study, which suggests greater drug exposure in cattle compared to sheep in this study. Coetzee et al [15] Wani et al [37] Allen et al [14] Allen et al [14] Gorden et al [21] Gorden et al [21] Shock et al [36] Warner et al [38] Warner et al [38] Publication…”
Section: Discussionmentioning
confidence: 99%